Educational Possibilities of Gamification in the Formation of Soft & Hard Skills among Students of Socionomic Professions - Savitska, Viktoriia; Gomotiuk, Oksana; Stefanyshyn, Olena; Rashid, Mohammad; Lengyelfalusy , Tomáš; Šurín , Stanislav (Journal of Education Culture and Society, 2025)
Aim. The purpose of the research is to establish a connection between the indicators of the effectiveness of soft and hard skills formation in students of socionomic professions through the use of gamification methods and to determine the impact of gamification on the development of individual soft and hard skills. Methods. The research methods are a content analysis of specialized literature, an online survey of students of socionomic professions using Google Forms, and a pedagogical experiment with comprehensive data processing. The research material consists of the empirical experience of gamification in developing soft and hard skills in students of socionomic professions, based on the creation of a virtual professional community f “School of Professional Growth,” during independent work. The interactive educational environment incorporates key components: game mechanics aligned with pedagogical outcomes, interactive tasks, and social interaction. Results. The results of the experiment confirmed the hypothesis: students in the experimental group showed increased interest in classes, were better adapted to non-standard situations, demonstrated flexibility of thinking, and improved their hard skills compared to the control group. Conclusion. The study reveals that gamification not only enhances student engagement and motivation but also fosters their professional growth by developing essential soft and hard skills for success in the socio-economic sphere. The integration within gamification of storylines, roles, characters, problem situations, and elements of unpredictability immerses students in professionally relevant situations, enhancing both their soft and hard skills.